Institute of ecological problems of the North of Ural Branch of Russian Academy of Sciences – the advanced post of ural academician science in the North - Боголицын, К. Г.; Bolotov, I. N.; Gorbova, N. S. (Perm Federal Research Centre Journal, 2013)
The paper gives general characteristics of Institute of Ecological Problems of the North of Ural Branch of Russian Academy of Sciences as one of the leading academic institutes in the Northern European Russia. Several results of scientific studies and organization activities for the last five years are illustrated. Information about international activities and field expeditions is given. Data on new scientific subdivisions (seismic observatory, biological museum, centre of molecular-genetic investigations) are represented. The nearest perspectives of the Institute development are considered. The article points out the significance of this organization as an advanced post of Ural academician science in the North.